Cigarette smoking decreases macrophage-dependent clearance to impact the biological effects of occupational and environmental particle exposures - Ghio, Andrew J.; Stewart, Matthew; Sangani, Rahul G.; Pavlisko, Elizabeth N.; Roggli, Victor L. (Frontiers in Public Health, 2025)
The retention of occupational and environmental particles in the lung is a primary determinant of biological effects. In the distal respiratory tract, particle clearance includes phagocytosis by alveolar macrophages (AMs), migration to the terminal bronchiole, and transport of AMs and particles by the mucociliary escalator. With increasing particle exposure, a focal collection of particle-laden macrophages results at the respiratory bronchiole (RB) which is that site in the clearance pathway demanding the greatest traverse by these cells after a commencement from the alveoli. With the greatest particle doses, there is “particle overload” and impaired mobility which is reflected by an excess accumulation of particle-laden macrophages throughout the RBs, alveolar ducts, and alveoli. With deposition of fibrous particles in the distal respiratory tract, the AM is unable to extend itself to enclose fibers with a major diameter of 10–20 microns or longer resulting in “frustrated phagocytosis” and longer retention times. Clearance pathways for particles are shared. There can be a summation of particle exposures with exhaustion in the capacity of the AMs for transport. Cigarette smoking (CS) is the greatest particle challenge humans encounter. Associated with its enormous magnitude, CS profoundly impacts the clearance pathways and subsequently interacts with other particle exposures to increase biological effects. Interstitial lung disease, pulmonary function, chronic obstructive pulmonary disease, infections, lung cancer, and mortality can be altered among smokers exposed to occupational and environmental particles (e.g., silica, coal mine dust, air pollution particles, other particles, and asbestos). It is concluded that both decreasing CS and controlling particle exposures are of vital importance in occupational and environmental lung disease.